2006
DOI: 10.1093/treephys/26.11.1413
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and photoassimilate transport during root hypoxia in Melaleuca cajuputi, a flood-tolerant species, and in Eucalyptus camaldulensis, a moderately flood-tolerant species

Abstract: We compared the photosynthetic and photoassimilate transport responses of Melaleuca cajuputi Powell seedlings to root hypoxia with those of Eucalyptus camaldulensis Dehnh. Control and hypoxia treated roots were maintained in a nutrient solution through which air or nitrogen was bubbled. Under root hypoxic conditions, seedlings of M. cajuputi, a flood-tolerant species, maintained height growth, whereas seedlings of E. camaldulensis, a moderately flood-tolerant species, showed markedly decreased height growth co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 46 publications
7
48
0
Order By: Relevance
“…Reduced mobilization of shoot starch reserves in soil moisture stress may have been due to reduced translocation rate. Kogawara et al (2006) reported reduced transport of photoassimilates and starch accumulation in leaves of Eucalyptus camaldulensis Dehnh 4 days after hypoxic treatment.…”
Section: Lar and Lccmentioning
confidence: 95%
See 2 more Smart Citations
“…Reduced mobilization of shoot starch reserves in soil moisture stress may have been due to reduced translocation rate. Kogawara et al (2006) reported reduced transport of photoassimilates and starch accumulation in leaves of Eucalyptus camaldulensis Dehnh 4 days after hypoxic treatment.…”
Section: Lar and Lccmentioning
confidence: 95%
“…Rate of photoassimilate transport to roots can decrease during flooding resulting in accumulation of starch in leaves (Kogawara et al 2006). Short periods of flooding followed by draining can result in a slow recovery of preflooded-photosynthetic rates as stomata reopen (Kozlowski and Pallardy 1997;Li et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of Alcohol dehydrogenase (ADH; EC 1.1.1.1) was quantified using the method of Kogawara et al (2006). The reaction mixture contained 50 mmol L -1 Tris-HCl (pH 8.0), 2 mmol L -1 DTT, 0.25 mmol L -1 NAD + , 30 µL of the enzyme extract, and 5 % ethanol.…”
Section: Hypoxia-responsive Enzyme Activitymentioning
confidence: 99%
“…BSP), Scots pine) (cf. Islam and Macdonald 2004;Sudachkova et al 2009;Repo et al 2016a) and broad-leaved species (White oak (Quercus alba L.), river red gum (Eucalyptus camaldulensis) (Gravatt and Kirby 1998;Kogawara et al 2006). In addition, the starch content in the leaves of pubescent birch was not affected by GW.…”
Section: Water Relations Photosynthesis and Carbohydratesmentioning
confidence: 99%